How a Humbler Science Becomes a Better Science - Sara Lumbreras; Laura Gismera; Lluis Oviedo (Religions, 2023)
Giving humility a key role in scientific practice and communication would improve its objective social function—that is, the production of knowledge about our world and its application to the improvement of the human condition—and its public acceptance. This article reviews the limits of science arising from systemic, epistemic, methodological, and individual limitations and links them to the phenomena in scientific practice that they originate from. The reflection invites us to consider science from the point of view of its limits in situations where there is difficulty in reaching a consensus but also when a consensus has indeed been achieved. Science and technology reflect who we are as individuals and as a society and inherit both our virtues and weaknesses. Humility is the key to getting technoscience that brings us closer to the truth and helps us advance toward improving the human condition. Humbler science becomes a better science.